A retrospective study of outcome of severe traumatic brain injury among adult patients in Emergency Department Hospital Universiti Sains Malaysia - Jusoh, Mardhiah (2017)
Traumatic brain injury (TBI) has become one of the major causes of death in this decade. Some of the associated and prognostic factors have been proven to have correlation with mortality in severe TBI in studies which were done earlier. However, some of them are yet still debatable. In Malaysia, the percentage of mortality of the patients presented with severe TBI is still high while a lot of survived patients had unfavorable outcome; persistently vegetative and severely disabled, as results of complications of primary and secondary brain injury. This study was done at Emergency Department (ED) of Hospital Universiti Sains Malaysia (HUSM) as HUSM is the center of referral for neurosurgical cases in Kelantan and nearby tertiary and district hospitals. In this study, the outcome of the adult patients with severe TBI were observed according to Glasgow Outcome Scale (GOS) upon discharge. This scale was used to assess the functional ability of the patients either low, moderate or severely disabled, persistently vegetative or death. Besides that, the aim of this study was also to determine the associated and prognostic factors that can predict the outcome of severe TBI patients. This include gender, age, clinical findings such as Glasgow Coma Scale (GCS) score, pupillary response, vital signs, blood investigations and primary CT brain findings.A retrospective study was done with 96 patients with severe TBI were enrolled. These patients were followed-up until discharge to identify their outcome. From 96 patients, one third of them which accounted 34.4% (33) died and 65.6% (63) survived. The survived patients; 31.3% (30) of them were discharged with good outcome (low disability), while both moderate and severely disabled, accounted about 15.6% (15) each. 3.1% (3) of them were discharged with vegetative state. Using the binary logistic regression model, a few prognostic factors were found to be significantly affecting the outcome of the severe TBI. These include, age, GCS score, abnormal pupillary response, presence of subdural hemorrhage (SDH) and midline shifts, total white count (TWC), pH, pCO2, HCO3, lactate and glucose level, prothrombin time (PT), INR and length of ICU and hospital stay. Whereby age, GCS score, abnormal pupillary response, duration of hospital stay and presence of midline shifts more than 5 mm on CT brain were factors that independently significant.